Teaching Reading Skills in Digital Classes: A Case Study at an Islamic Secondary School - Habib, Ibnu; Prasestyarini, Aryati (Universitas Muhammadiyah Surakarta, 2025)
This study aims to investigate the effectiveness of digital classrooms in English teaching, more specifically in developing students' reading skills of English language instruction at an Islamic secondary high school in Surakarta City. In this study the researcher examines how digital media supports English language learning, especially in the reading domain and its role in developing students' vocabulary knowledge, sentence-level comprehension. The study adopted mixed-methods case study design. Participants included students who attended two digital class sessions and one teacher responsible for instructional delivery. The data were collected from students' performance on multiple-choice comprehension tests based on the topic from English reading material, and from an in depth interview with the teacher. Quantitative data were obtained from one topic with two assessments and were thematically analyzed to contextualize instructional strategies and challenges in digital learning. The integration of quantitative and qualitative findings enabled triangulation and provided an understanding of how digital media supports English language learning. This study contributes to the literature on educational technology, by documenting how English digital classroom programs are implemented in Islamic secondary schools. Practically the research provided insights for teacher training, curriculum development, and afforded the researcher substantive experience across all stages of the research process.